Business Assignments / Eight advanced case studies with video - Casler Ken; Palmer David; Woodridge Teresa (Oxford University Press, 1989)
This book is a set of eight international case studies with video for advanced learners of Business English. Introduction, IPSA, Cougar, Chocolates Memlinck, HAL Information Systems, Editions Comenius, Royce-Lytton, Jaudel France, Microtron Italy.